Indole-3-acetic acid promotes wound healing of potato tubers by activating auxin signaling and phenylpropanoid metabolism - Lirong Yu; Tongtong Cui; Pengdong Xie; Botao Bai; Ruirui Yang; Ye Han; Yi Wang; Xin Li; Yang Bi; Dov Prusky (Postharvest Biology and Technology, 2026)

Numerical simulation of thermal-hydraulic-chemical multi-physical field coupling for large-scale experimental models of CO2 hydrate sequestration - Lei Wang; Xianjie Yan; Yang Ge; Ruirui Li; Zhaoran Wu; Jinyan Lan; Jiefeng Liu (Fuel, 2026)

Hydrological switching mechanism: Converting steep cropland to pasture mitigates nutrient loss by altering runoff pathways - Yanan Chen; Yuan Zhuang; Ruirui Yan; Peizhi Yang; Shimin Liu; Lianhai Wu; Yang Liu; Junbo Xiong; Jingwei Jin; Xiaoping Xin (CATENA, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Achieving 96.6% energy-storage efficiency in Nd-doped tungsten-bronze ceramics through A-site vacancy engineering - Zhihong Wang; Yangfei Gao; Bian Yang; Mei Bai; Xiangran Pei; Hai Ci; Ruirui Kang; Junbo Xu; Yingying Zhao; Mengyao Guo; Fei Li; Xiaojie Lou (Chemical Engineering Journal, 2026)

Trade-offs among pear yield, fruit quality, and reactive nitrogen losses under water–nitrogen management across contrasting soil textures - Yanlong Li; Ruirui Du; Mingde Sun; Yang Wu; Zhenxu Liang; Qinghua Wang; Jun Liu; Songzhong Liu (Journal of Environmental Management, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

Coupling heterovalent complementary doping with surface tailoring for stable O3-type layered oxide cathodes - Yang Liu; Haoji Wang; Yang Sun; Yingchang Yang; Wei Shi; Kaixu Yang; Jing Chen; Ruirui Wang; Xinyao Yang; Yanxu Wang; Haibiao Ning; Qifu Shi; et al. (Chemical Engineering Journal, 2026)

Constructing atomic-scale proton channels in polymeric carbon nitride via synergistic oxygen and carbon defects for efficient CO2 photoreduction - Ruirui Wang; Yiming Wang; Jinhang Liu; Huixiong Jiang; Ran Wang; Yang Wang; Shunhang Wei; Xiaoxiang Xu; Yawei Wang (Chemical Engineering Journal, 2026)

Anaerobic digestion of acidic waste mash via light-assisted & hemin-acclimated inoculum: A case study of cassava alcohol stillage - Yang Wang; Dong Guo; Junlin Ji; Zhihan Luo; Zhicheng Zhu; Ruirui Hou; Kai Wu; Hong Yang; Jinhe Jiang; Fang Yin (Biomass and Bioenergy, 2026)

Construction of an Oral Vaccine Based on Multiple Antigens of African Swine Fever Virus Displayed on the Surface of Bacillus Subtilis Spores and Study of its Immune Effect in Rats - Tian Yang; Maomao Li; Zhuoxuan Wu; Jiahua Cheng; Ningyin Si; Weiping Du; Ruirui Wang; Yuhong Lyu (Current Microbiology, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Photoperiod-dependent protein and lipid biosynthesis in Auxenochlorella pyrenoidosa cultivated using food waste hydrolysate - Huaying Tang; Haotian Xie; Qiao Kuang; Ying Huang; Fangfang Zhang; Ruirui Yang; Guangbin Ye; Xiang Wang; Yufeng Yang (Journal of Environmental Management, 2026)

Bioactive earthworm proteins and peptides from traditional Chinese medicine: structural diversity, biomedical applications, and emerging biomanufacturing strategies - Hanzhi Weng; Fengling Yang; Zhiliang Hou; Siyan Zhou; Jie Lu; Xiaoyuan Sun; Ruirui Xu; Zhen Kang (Systems Microbiology and Biomanufacturing, 2026)

Metabolic engineering of mannitol metabolism to improve protein production in Fusarium venenatum - Xizhen Liu; Longxue Ma; Ruirui Zhang; Yang Yang; Wuxi Chen; Liucheng Long; Yu Zheng; Demao Li (Systems Microbiology and Biomanufacturing, 2026)

Integrative networks regulating tomato fruit locule number through shoot apical meristem size control: bridging genetic, phytohormonal and environmental factors - Tianpeng Zhang; Xinghong Yang; Subo Tian; Peipei Yin; Ruirui Xu (Planta, 2026)

Advances in the roles of SCOOP peptides and the receptor-like kinase MIK2 in plant stress responses - Jiaxuan Zhu; Ruili Lv; Ruirui Yang; Yushi Luan (Plant Cell Reports, 2026)

Rhizosphere metabolic responses to soil acidification and their implications for nutrient uptake in eggplant - Tianqi Wang; Muhammad Awais; Xiaoyang Yu; Baiyi Bai; Zhen Wang; Ruirui Zhang; Lijie Yu; Dan Zhao; Xing Li; Ping Zhang; Roland Bol; Lijuan Yang (Rhizosphere, 2026)

Laponite-reinforced marine bioinspired injectable self-healing adhesive chitosan-based hydrogel for infected wounds - Ruirui Guan; Yuhui Su; Shanshan Li; Shuo Yang; Xiaoyun Li; Xiaoying Wang (Carbohydrate Polymers, 2026)

Comparative analysis of ecological corridor evolution and environmental quality in an urban small watershed: A case study of the Jiyu River, Hefei (2019–2024) - Guoxu Chen; Kaidi Yang; Ruirui Li; Li Cao; Xincheng Gao; Yongqi Fan; Kesheng Zuo; Li’ao Quan (Urban Ecosystems, 2026)

Reprogramming the intrinsic capsular polysaccharide biosynthesis pathway for efficient secretory production of chondroitin in Escherichia coli Nissle 1917 - Shan Hu; Siyan Zhou; Mingming Zheng; Haibo Xiong; Guobin Yin; Fengling Yang; Ping Dong; Jian Chen; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2026)

The papain-like cysteine proteases (PLCP) in tomato: Identification, expression analysis, and functional characterization of SlRD19B under salt stress - Jiaxuan Zhu; Ruirui Yang; Yan Li; Ruili Lv; Huimin Li; Yao Yao; Yushi Luan (Plant Science, 2026)

Enhancement of calcium oxide on hydrogen production and degradation of polylactic acid microplastics in anaerobic fermentation - Xiaoxuan Zhu; Ruirui Shang; Xi Yang; Chuanzheng Song; Hui Mu; Chunhui Zhao; Huanhuan Guo; Yongfang Zhang (Journal of Environmental Management, 2026)

N-halamine-grafted MIL-125-NH2(Ti) as a long-lasting chlorine reservoir for round-the-clock decontamination of Aspergillus aerosols - Ruirui Hou; Hao Yang; Fengming Hou; Yihang Li; Zhipeng Guo; Jin Li; Wei Wei; Ang Wei (Chemical Engineering Journal, 2026)

Functional analysis of SlCDPK12 and its interacting protein SlACS11 in the regulation of tomato resistance to Phytophthora infestans - Yan Li; Jiaxuan Zhu; Ruili Lv; Zhengjie Wang; Huimin Li; Ruirui Yang; Yushi Luan (Journal of Plant Physiology, 2026)

Scalable ergothioneine production via integrating chemical methylation and rhodanese-catalyzed CS bond formation - Jie Lu; Xiaoyuan Sun; Hanzhi Weng; Weiquan Ding; Fengling Yang; Guochen Du; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

PtRu synergistic effect facilitates hydrogenation of liquid organic hydrogen carrier in aqueous phase under ambient pressure - Shuhan Lu; Jiao He; He Jiang; Yixiao Wang; Ruirui Hu; Xiang Gong; Bin Wang; Chunhai Yi; Fusheng Yang; Tao Fang (Chemical Engineering Journal, 2026)

Bimetallic chloride in situ etching of NiFe alloy substrate to synthesize porous coral structure catalyst for efficient oxygen evolution reaction - Yu Zhang; Yaoxia Yang; Biaobiao Lu; RuiRui Zhang; Fuxing Zhou; Dongfei Sun; Qingtao Wang; Jian Li; Ziqiang Lei (Fuel, 2025)

Unveiling the oxidation-reduction mechanism of the Arsenazo III-U(VI) complexes by synergistic electron beam irradiation and Cu-Fe MOFs: Combined kinetic and DFT studies - Ruirui Wang; Xiaomao Zhou; Dan Liu; Jiahui Li; Long Zhao; Zhen Dong; Buri Qi; Miao Yang (Chemical Engineering Journal, 2025)

The receptor-like kinase SlLRR-RLK94 as a positive regulator of tomato resistance to Phytophthora infestans - Jiaxuan Zhu; Yan Li; Ruirui Yang; Zhiyuan Xue; Ruili Lv; Hongbo Wei; Zhengjie Wang; Ruiming Wang; Yushi Luan (Plant Cell Reports, 2025)

Evaluation of the Degradation Effect of Zearalenone in feed by Bacillus amyloliquefaciens H6 and its Detoxification in Mice - Ruolin Wang; Kaiwei Geng; Yuxuan Liu; Yang Liu; Yujie Gong; Ruirui Jiang; Yadong Tian; Xiangtao Kang; Xiangli Sun; Yanbin Wang (Current Microbiology, 2025)

Multiscale phenotyping of grain crops based on three-dimensional models: A comprehensive review of trait detection - Jiangtao Qi; Fangfang Gao; Yang Wang; Weirong Zhang; Sisi Yang; Kangkang Qi; Ruirui Zhang (Computers and Electronics in Agriculture, 2025)

National-scale genomic diagnosis of rare diseases in China - Xiaodong Luan; Ye Jin; Liping Guan; Peng Liu; Hailong Feng; Dingding Zhang; Jingdan Chen; Weida Liu; Fangyuan Li; Anqi Wang; Kun Zhao; Ruirui He; et al. (Science Bulletin, 2025)

Atrazine-induced hippocampal neurotoxicity: Involvement of Drp1-mediated mitochondrial fission - Jingran Yang; Ling Qi; Cheng Zhang; Ruirui Ding; Haoran Bi; Peng Li; Zhipeng Qi; Qiao Niu; Weiyi Song; Jianan Li (Chemico-Biological Interactions, 2025)

Synthesis and biological evaluation of triazole alcohols containing an indole-3-methyl(phenyl)amino side chain against fluconazole-resistant Candida albicans - Zefei Fan; Lijiao Yang; Jidong Wang; Yafei Hou; Fei Zou; Tianyu Zhang; Yongyan Fu; Yue Zhang; Ruirui Wang; Shichong Yu; Guanghui Ni (Medicinal Chemistry Research, 2025)

Engineering Komagataella phaffii cell factories for the production of chondroitin sulfate A with high sulfation degree - Haibo Xiong; Xiaogang Yang; Weijiao Zhang; Litao Hu; Gege Liu; Guocheng Du; Jian Chen; Jianghua Li; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2025)

Exogenous spermidine promotes the formation of the closing layer at potato tuber wounds by inducing polyamine synthesis and phenylpropanoid metabolism - Ying Wang; Ruirui Yang; Qihui Wang; Pengdong Xie; Xiaojing Wang; Yongcai Li; Dov Prusky; Ye Han; Yang Bi (Postharvest Biology and Technology, 2025)

Cytokinin signaling pathway involved in 6-BA-induced wound healing in potato tubers - Ruirui Yang; Qihui Wang; Ying Wang; Xuejiao Zhang; Zixiong Ye; Chunwei Han; Jiaojuan Wang; Yongcai Li; Dov Prusky; Yang Bi; Ye Han (Postharvest Biology and Technology, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Exploring the mechanisms of hippocampal neurotoxicity induced by cypermethrin: Insights from integrated miRNA-seq and mRNA-seq analysis - Jingran Yang; Ruirui Ding; Ling Qi; Haoran Bi; Jianan Li (Environmental Toxicology and Pharmacology, 2025)

Long-term reconstruction of NO2 photolysis rate coefficients using machine learning and its impact on secondary pollution: A case study in a megacity of the Sichuan Basin, China - Tong Li; Song Liu; Dongyang Chen; Ruirui Zhang; Hefan Liu; Danlin Song; Qinwen Tan; Hongbin Jiang; Li Zhou; Fumo Yang (Atmospheric Pollution Research, 2025)

Characterization of PAMP-induced peptides and mechanistic insights into SlPIP2-mediated defense in tomato - Ruirui Yang; Hongbo Wei; Jiaxuan Zhu; Zhiyuan Xue; Siya Zeng; Jun Meng; Yushi Luan (Plant Cell Reports, 2025)

Research progress on the synergistic effect and its mechanisms of antidepressants and antibiotics against resistant pathogens - Lihong Ding; Xia Chen; Yanli Lv; Qianyu Peng; Ruirui Wang; Bo Yang; Lianhua Wei (Archives of Microbiology, 2025)

Antagonistic Effects of Nitric Oxide and Far-Red Light on Sorbus pohuashanensis Embryo Germination - Ruirui Wang; Mengfan Wang; Ling Yang (Journal of Plant Growth Regulation, 2025)

The novel biochar-based organic semiconductor toward broadband and direct radicals transfer enhanced photocatalytic degradations - Yuchen Wang; Qianqian Pan; Songlin Cai; Liwei Liang; Liangsheng Chen; Ruirui Zhang; Liu Liu; Yanzhen Yin; Tao Yang; Hongxiang Zhu; Tao Liu (Journal of Environmental Management, 2025)

Muti-network active aerogel based on PVA, bacterial cellulose, and sodium alginate: Characterization, kinetics studies, and application for mutton preservation - Xi Zhou; Fangqu Wang; Yang Yu; Ruirui Guo; Xinran You; Xiaomei Xiang; Xiaojing Fan; Yabin Niu; Xuejiao Wang; Xianchao Feng; Lin Chen (Food Hydrocolloids, 2025)

YOLO-detassel: Efficient object detection for Omitted Pre-Tassel in detasseling operation for maize seed production - Jiaxuan Yang; Ruirui Zhang; Chenchen Ding; Liping Chen; Yuxin Xie; Hong Ou (Computers and Electronics in Agriculture, 2025)

Role of benzothiadiazole in regulating reactive oxygen species and inhibiting cap opening in Agaricus bisporus during storage - Ruirui Yang; Yanan Wei; Hui Peng; Ting Wang; Jianmin Yun; Yan Yin; Yang Bi (Postharvest Biology and Technology, 2025)

Warmer summers have the potential to affect food security by increasing the prevalence and activity of Actinobacteria - Yuanyuan Bao; Jan Dolfing; Zhiying Guo; Jie Liu; Xianzhang Pan; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Lixia Zhang; Ruirui Chen; Xin Li; Youzhi Feng (European Journal of Soil Biology, 2025)

The hygienic insecticide dimefluthrin induced neurodevelopmental deficits and behavioral disorders in zebrafish (Danio rerio) larvae - Ruirui Li; Wenping Xu; Qingfeng Li; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Environmental Research, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

The effect of stem contact fermentation on the quality of Cabernet Sauvignon and Merlot wines from Yantai, China - Ruirui Li; Dongyue Yang; Zhiyu Li; Xiaohong Tang; Ke Zhong; Yan Ding; Xiaomei Han; Xueqiang Guan; Yuxia Sun (Food Bioscience, 2025)

Hydrogen-rich water enhanced salt tolerance in tomato seedlings by regulating strigolactone biosynthesis genes SlMAX1 and SlD27 - Fujin Ye; Hua Fang; Li Feng; Meimei Shi; Ruirui Yang; Weibiao Liao (Plant and Soil, 2025)

Electron beam irradiation in collaboration with Bi-Fe MOFs for oxidation of bisphenol A and reduction of Cr(VI): Kinetics, DFT calculation and mechanism - Dan Liu; Junhui He; Ruirui Wang; Zhen Zhao; Zhen Dong; Qiburi Bao; Long Zhao; Miao Yang (Journal of Environmental Chemical Engineering, 2024)

Prenatal exposure to PM2.5 and its composition on child growth trajectories in the first two years: A prospective birth cohort study - Ruirui Ma; Peng Wang; Yuanyuan Zhu; Lei Zhang; Dongjian Yang; Min Xu; Ziyu Shao; Peng Zhu (Environmental Pollution, 2024)

Targeting STING oligomerization with licochalcone D ameliorates STING-driven inflammatory diseases - Yinghui Zhang; Yadan Liu; Bing Jiang; Lifan Chen; Jie Hu; Buying Niu; Jie Chang; Zisheng Fan; Jingyi Zhou; Yajie Wang; Dan Teng; Ning Ma; et al. (Science China Life Sciences, 2024)

Grape Seed Proanthocyanidins Protect Pancreatic β Cells Against Ferroptosis via the Nrf2 Pathway in Type 2 Diabetes - Haiyan Li; Haowei Zhang; Tongling Wang; Liyuan Zhang; Hao Wang; Heng Lu; Ruirui Yang; Yusong Ding (Biological Trace Element Research, 2024)
Pancreatic β cell damage is the primary contributor to type 2 diabetes mellitus (T2DM); however, the underlying mechanism remains nebulous. This study explored the role of ferroptosis in pancreatic β cell damage and the protective effects of grape seed proanthocyanidin extract (GSPE). In T2DM model rats, the blood glucose, water intake, urine volume, HbA1c, and homeostasis model assessment-insulin resistance were significantly increased, while the body weight and the insulin level were significantly decreased, indicating the successful establishment of the T2DM model. MIN6 mouse insulinoma β cells were cultured in high glucose and sodium palmitate conditions to obtain a glycolipid damage model, which was administered with GSPE, ferrostatin-1 (Fer-1), or nuclear factor erythroid 2-related factor 2 (Nrf2) small interfering (si) RNA. GSPE and Fer-1 treatment significantly improved pancreatic β-cell dysfunction and protected against cell death. Both treatments increased the superoxide dismutase and glutathione activity, reduced the malondialdehyde and reactive oxygen species levels, and improved iron metabolism. Furthermore, the treatments reversed the expression of ferroptosis markers cysteine/glutamate transporter (XCT) and glutathione peroxidase 4 (GPX4) caused by glycolipid toxicity. GSPE treatments activated the expression of Nrf2 and related proteins. These effects were reversed when co-transfected with si-Nrf2. GSPE inhibits ferroptosis by activating the Nrf2 signaling pathway, thus reducing β-cell damage and dysfunction in T2DM. Therefore, GSPE is a potential treatment strategy against T2DM. Graphical Abstract

Anaerobic fermentation for hydrogen production and tetracycline degradation: Biodegradation mechanism and microbial community succession - Ruirui Shang; Wenhan Chen; Dong Wei; Xiang Li; Mengyao Tang; Zihao Yang; Yongfang Zhang (Science of The Total Environment, 2024)

Dissolved ammonia catalyzes proto-dolomite precipitation at Earth surface temperature - Ruirui Meng; Zuozhen Han; Xiao Gao; Yanyang Zhao; Chao Han; Yu Han; Renchao Yang; Shuangjian Li; Fang Liu; Maurice E. Tucker; Yanjing Chen (Earth and Planetary Science Letters, 2024)

Quenching-induced amorphisation and configuration transformation for the enhanced electrochemical performance of poly(vinylidene fluoride-hexafluoropropylene)-based solid electrolytes - Yaguang Zhang; Jianxun Zou; Ruirui Chang; Zixuan Min; Shuping Dong; Zhijia Tang; Xuandu Li; Jingjing Tang; Juan Yang; Xiangyang Zhou (Chemical Engineering Journal, 2024)

Construction of foam-like carbon microspheres with controllable pseudo-graphitic domains: Synergistic enhancement of K-ion adsorption/intercalation storage - Qingjuan Ren; Lei Yan; Xuewen Yu; Wenhua Lei; Zhongyu Sun; Ruirui Hao; Jianzeng Yang; Zhiqiang Shi (Chemical Engineering Journal, 2024)

Fine-grained method for determining size and velocity distribution patterns of flat-fan nozzle-atomised droplets based on phase doppler interferometer - Ruirui Zhang; Peng Hu; Longlong Li; Qing Tang; Jiaxuan Yang; Jiajun Yang; Liping Chen (Computers and Electronics in Agriculture, 2024)

Natural pyrethrins induced developmental toxicity of zebrafish swim bladder in vivo and genotoxicity of lung cells in vitro - Ruirui Li; Cheng Zhang; Wenping Xu; Liming Tao; Jiagao Cheng; Zhong Li; Yang Zhang (Toxicology in Vitro, 2024)

Cardiotoxicity risk induced by sanitary insecticide Dimefluthrin - Ruirui Li; Ning Zhou; Cheng Zhang; Mengqi Wu; Wenping Xu; Jiagao Cheng; Liming Tao; Zhong Li; Yang Zhang (Chemosphere, 2024)

Hydrogen gas: A new fresh keeping agent of perishable horticultural products - Hua Fang; Fujin Ye; Ruirui Yang; Dengjing Huang; Xinfang Chen; Chunlei Wang; Weibiao Liao (Food Chemistry, 2024)

Zirconium‑cerium modified polyvinyl alcohol/NaCMC biocomposite film: Synthesis of films through high-speed shear assisted technique and removal fluoride from water - Ruirui Yang; Fuqing Bai; Liping Mei; Wei Guo; Huanhuan Qiao; Guijie Chen; Junsheng Liu; Fei Ke; Chuanyi Peng; Ruyan Hou; Xiaochun Wan; Huimei Cai (Carbohydrate Polymers, 2024)

Synthesis, structure-activity relationship and evaluation of antifungal activity of tryptanthrin derivatives against drug-resistant Candida albicans - Yandan Wu; Luyi Jiang; Ruina Liu; Lijiao Yang; Fei Zou; Tianyu Zhang; Zefei Fan; Tianbao Zhang; Huan Yang; Shuyun Yin; Ruirui Wang; Ganpeng Li; et al. (Medicinal Chemistry Research, 2024)

Enhancing the expression of chondroitin 4-O-sulfotransferase for one-pot enzymatic synthesis of chondroitin sulfate A - Weijiao Zhang; Ping Zhang; Hao Wang; Ruirui Xu; Zhuan Xie; Yang Wang; Guocheng Du; Zhen Kang (Carbohydrate Polymers, 2024)

Construction of immobilized enzyme cascades for the biosynthesis of nucleotide sugars UDP-N-acetylglucosamine and UDP-glucuronic acid - Jialian Li; Yanlai Liu; Litao Hu; Ruirui Xu; Weijiao Zhang; Shan Hu; Yang Wang; Guocheng Du; Zhen Kang (Systems Microbiology and Biomanufacturing, 2024)

Understanding the effect of plastic food packaging materials on food flavor: A critical review - Fuqing Bai; Guijie Chen; Yanan Hu; Yuexin Liu; Ruirui Yang; Junsheng Liu; Ruyan Hou; Hongfang Li; Xiaochun Wan; Huimei Cai (Trends in Food Science & Technology, 2024)

Shared xerophytic genes and their re‐use in local adaptation to aridity in the desert plant Gymnocarpos przewalskii - Ruirui Fu; Yuxiang Zhu; Ying Liu; Zhaoping Yang; Ruisen Lu; Yingxiong Qiu; Martin Lascoux; Pan Li; Jun Chen (Molecular Ecology, 2024)
In order to thrive and survive, plant species need to combine stability in the long term and rapid response to environmental challenges in the short term. The former would be reflected by parallel or convergent adaptation across species, and the latter by pronounced local adaptation among populations of the same species. In the present study, we generated a high‐quality genome and re‐sequenced 177 individuals for Gymnocarpos przewalskii , an important desert plant species from North‐West China, to detect local adaptation. We first focus on ancient adaptation to aridity at the molecular level by comparing the genomic data of 15 species that vary in their ability to withstand aridity. We found that a total of 118 genes were shared across xerophytic species but absent from non‐xerophytic species. Of the 65 found in G. przewalskii , 63 were under purifying selection and two under positive selection. We then focused on local adaptation. Up to 20% of the G. przewalskii genome showed signatures of local adaptation to aridity during population divergence. Thirteen of the selected shared xerophytic genes were reused in local adaptation after population differentiation. Hence, only about 20% of the genes shared and specific to xerophytic species and associated with adaptation to aridity were later recruited for local adaptation in G. przewalskii .

Rare earth cation-modified X zeolites for isobutane alkylation: The influence of ionic radius - Zhiqiang Yang; Xinxin Li; Ruirui Zhang; Ruixia Liu (Fuel, 2024)

Environmentally relevant exposure to cotinine induces neurobehavioral toxicity in zebrafish (Danio rerio): A study using neurobehavioral and metabolomic approaches - Dan Yang; Wenfei Yu; Jiajia Qu; Yuexing Shen; Jingtong Yu; Ruirui Meng; Zhen Tao; Jiangfei Chen; Wei Du; Haitong Zhe Sun; Yunhui Zhang; Yuanchen Chen; et al. (Environmental Pollution, 2024)

UV-C radiation promoted flavonoid synthesis during early healing in potato tuber wounds with the possible involvement of ABA and related transcription factor regulation - Xuejiao Zhang; Xiaoyuan Zheng; Ruirui Yang; Qihui Wang; Lu Bai; Di Gong; Ye Han; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2024)

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

ERS Mediated by GRP-78/PERK/CHOP Signaling Is Involved in Fluoride-Induced Ameloblast Apoptosis - Li Jinyi; Yang Keyu; Dai Shanshan; He Shuyang; Liu Ruirui; Guo Qingyu; Liu Fei (Biological Trace Element Research, 2024)

A nested case-control study of serum zinc and incident diabetes among Chinese adults: Effect modifications and mediation analysis - Jingli Yang; Zhiyuan Cheng; Desheng Zhang; Tongzhang Zheng; Chun Yin; Simin Liu; Lizhen Zhang; Zhongge Wang; Yufeng Wang; Ruirui Chen; Qian Dou; Yana Bai (Science of The Total Environment, 2024)

Identification of point and nonpoint emission sources of neonicotinoid pollution in regional surface water - Yuanchen Chen; Jun Ling; Wenfei Yu; Li Zhang; Ruxin Wu; Dan Yang; Jiajia Qu; Hangbiao Jin; Zhen Tao; Yuexin Shen; Ruirui Meng; Jingtong Yu; et al. (Water Research, 2024)

Reliability service-based strategies for improving electricity retailer competitiveness using a novel heuristic algorithm - Jichun Liu; Ruirui Huang; Xiao Xu; Yuyan Yang; Junyong Liu (Journal of Cleaner Production, 2024)

Effects of oyster shells on maturity and calcium activation in organic solid waste compost - Wanlin Song; Yang Zeng; Jiali Wu; Qian Huang; Ruirui Cui; Derui Wang; Yuxue Zhang; Min Xie; Dawei Feng (Chemosphere, 2023)

Metabolomics reveals antioxidant and antifungal functions of flavonoids in the early stage wounded potato tubers - Xiaoyuan Zheng; Xuejiao Zhang; Jinmei Zhao; Ruirui Yang; Lu Bai; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Exosomal circCNOT6L Regulates Astrocyte Apoptotic Signals Induced by Hypoxia Exposure Through miR99a-5p/SERPINE1 and Alleviates Ischemic Stroke Injury - Wanting He; Lian Gu; Jialei Yang; Ruirui Zhang; Jianxiong Long; Wenyi Peng; Baoyun Liang; Lulu Zhu; Miao Lv; Aruo Nan; Li Su (Molecular Neurobiology, 2023)

Food-borne botulism from homemade sauce leading to cardiac arrest: A family case series with literature review - Weiying Yang; Dongyue Jiang; Ruirui Li; Lichao Sun (Toxicon, 2023)

The higher the cuteness the more it inspires garbage sorting intention? - Fuqiang Tan; TingYue Kuang; DaJun Yang; Zemin Jia; RuiRui Li; Liangyu Wang (Journal of Cleaner Production, 2023)

Ferulic acid treatment enhances the synthesis, transport and deposition of suberin polyaliphatic monomers on potato tuber wounds - Ruirui Yang; Ye Han; Xuejiao Zhang; Qihui Wang; Xiaoyuan Zheng; Ying Wang; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Meyerozyma guilliermondii promoted the deposition of GSH type lignin by activating the biosynthesis and polymerization of monolignols at the wounds of potato tubers - Xiaoyuan Zheng; Xuejiao Zhang; Jinmei Zhao; William Oyom; Haitao Long; Ruirui Yang; Lumei Pu; Yang Bi; Dov Prusky (Food Chemistry, 2023)

UV-C irradiation maintains cell membrane integrity at wounds of potato tubers during healing by regulating ROS homeostasis and increasing antioxidant activity - Xuejiao Zhang; Xiaoyuan Zheng; Ye Han; Ruirui Yang; Qihui Wang; Di Gong; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Pyrolysis of Ca/Fe-rich antibiotic fermentation residues into biochars for efficient phosphate removal/recovery from wastewater: Turning hazardous waste to phosphorous fertilizer - Mingdong Zhang; Qinpeng Chen; Ruirui Zhang; Yuting Zhang; Feipeng Wang; Minzhen He; Xiumei Guo; Jian Yang; Xiaoyuan Zhang; Jingli Mu (Science of The Total Environment, 2023)

Melatonin facilitates the deposition of suberin polyphenolic and lignin at wounds of potato tubers by mediating nitric oxide and reactive oxygen species - Qihui Wang; Ye Han; Ruirui Yang; Xuejiao Zhang; Yatong Zhu; William Oyom; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Spatial–temporal dynamics of the built environment toward sustainability: A material stock and flow analysis in Chinese new and old urban areas - Dong Yang; Mengyuan Dang; Jing Guo; Lingwen Sun; Ruirui Zhang; Feng Han; Feng Shi; Qian Liu; Hiroki Tanikawa (Journal of Industrial Ecology, 2023)
The urban built environment has accumulated massive amounts of resources, which is the main “hot spot” of construction materials and energy consumption in cities. To effectively monitor and manage resources use and waste disposal toward sustainability, this study intended to explore different metabolic paths of the urban built environment, as well as strategies for new and old urban areas separately with the help of material stock and flow analysis. Based on snapshots of 2003, 2010, and 2017 and combined with big data, a four‐dimensional geographic information system buildings database of Lixia District in Jinan, China, was compiled for bottom‐up stock modeling. Finally, the environmental impact assessment of the buildings’ demolition and disposal stage was carried out. The results showed that the building material stock was 142.31 Mt in 2017, with an increase of 69% from 2003. The reinforced concrete buildings increased rapidly from 2003 to 2017, especially in new urban areas, which has boosted demand for steel and cement by more than 150% during these 15 years. The material stock of the old urban area tends to be saturated, whereas the new urban area has experienced a rapid expansion with the material inflow four times as large as the material outflow. Potential recycling of waste concrete can reduce the generation of building demolition waste by 50%, save 0.15 km 2 of land occupation, increase raw material substitution by nearly 10 times, and reduce CO 2 emissions by 2.5 times.

Uric acid accumulation in the kidney triggers mast cell degranulation and aggravates renal oxidative stress - Mingkang Zhang; Ruirui Cui; Yan Zhou; Yanrong Ma; Yongwen Jin; Xueyan Gou; Jinru Yang; Xin’an Wu (Toxicology, 2023)

Enhanced energy storage performance of Bi0.5Na0.5TiO3-based ceramics via grain tuning and relaxor construction - Ruirui Kang; Zepeng Wang; Weijie Yang; Yingying Zhao; Lixue Zhang; Xiaojie Lou (Chemical Engineering Journal, 2023)

Bionic morphological design and interface-free fabrication of halfmoon microrobots with enhanced motion performance - Dong Liu; Dayin Sun; Jiaxin Zhou; Haoran Liu; Ruirui Guo; Bin Wang; Wenjun Ma; Zhenzhong Yang; Yuan Lu (Chemical Engineering Journal, 2023)

Association between short-term exposure to ambient air pollution and number of outpatient Helicobacter pylori infection visits - Lizuo Ma; Zhijing Lin; Jiaoxue Wang; Ruirui Ye; Yuefang Li; Ping Chen; Zhi Yuan; Liyan Yang; Lin Miao; Jiehua Li (Environmental Science and Pollution Research, 2022)

Secondary donor-derived CD19 CAR-T therapy is safe and efficacious in acute lymphoblastic leukemia with extramedullary relapse after first autologous CAR-T therapy - Delin Kong; Tingting Yang; Jia Geng; Ruirui Jing; Qiqi Zhang; Guoqing Wei; He Huang; Yongxian Hu (Journal of Zhejiang University-SCIENCE B, 2022)

What matters most to the material intensity coefficient of buildings? Random forest‐based evidence from China - Ruirui Zhang; Jing Guo; Dong Yang; Hiroaki Shirakawa; Feng Shi; Hiroki Tanikawa (Journal of Industrial Ecology, 2022)
Material intensity coefficient (MIC) is vital for material stock accounting in the field of industrial ecology. However, the categorization of MIC varies across regions especially for buildings that diverge greatly along the history and space aspect, and acquisition of MIC data and building information have always been a challenge in related studies. In this study, the state‐of‐art ensemble model “Random Forest” was developed on Chinese buildings to identify the impact of four building attributes (building structure, construction year, use type, and region) on MIC, and these features’ importance was further assessed by considering variable correlations. The features’ importance and their individual effects on MIC were intuitively revealed by depicting the partial dependence plots. Finally, a set of hierarchical MIC values was estimated by integrating the order of four variables’ importance and a quick MIC calculator was provided. Results showed that building structure is the most influential attribute for MIC, followed by the construction year, use type, and region, successively. The RF‐based MIC values allow researchers to apply it to material stock and flow analysis by choosing a specific building feature(s) in the MIC calculator, which is (are) available in building physical inventory data. This study provides a method that could help researchers locate key influencing variables and give insights into the comparability of MIC research across regions and play an important role in developing urban mining and circular economy strategies.

Evaluation and analysis of heavy metals in iron and steel industrial area - Xu Zhang; Huanhuan Yang; Ruirui Sun; Meihua Cui; Ning Sun; Shouwen Zhang (Environment, Development and Sustainability, 2022)

Reshaping of the soil microbiome by the expansion of invasive plants: shifts in structure, diversity, co-occurrence, niche breadth, and assembly processes - Changchao Li; Huaizhi Bo; Bingzhong Song; Xiaocui Chen; Qingqing Cao; Ruirui Yang; Shuping Ji; Lifei Wang; Jian Liu (Plant and Soil, 2022)

Apigenin inhibits growth of melanoma by suppressing miR-512-3p and promoting the G1 phase of cell cycle involving the p27 Kip1 protein - Qun Xie; Ruirui Zhang; Dandan Liu; Jing Yang; Qiang Hu; Chao Shan; Xiaohan Li (Molecular and Cellular Biochemistry, 2022)

PLC1 and H2O2 Mediated the Allelopathic Effect of Oridonin on Root Growth in Arabidopsis thaliana - Yue Zhang; Yanhuang An; Ning Yang; Wei Wang; Ruirui Liu; Run Gao; Yaping Zhou (Journal of Plant Growth Regulation, 2022)

The content, composition, and influencing factors of organic carbon in the sediments of two types of constructed wetlands - Ruirui Yang; Jiaohui Fang; Qingqing Cao; Di Zhao; Junyu Dong; Renqing Wang; Jian Liu (Environmental Science and Pollution Research, 2021)

Adverse effects of short-term personal exposure to fine particulate matter on the lung function of patients with chronic obstructive pulmonary disease and asthma: a longitudinal panel study in Beijing, China - Ruirui Duan; Hongtao Niu; Tao Yu; Ke Huang; Han Cui; Chen Chen; Ting Yang; Chen Wang (Environmental Science and Pollution Research, 2021)

Black phosphorus nanosheets and docetaxel micelles co-incorporated thermoreversible hydrogel for combination chemo-photodynamic therapy - Ruirui Li; Linwei Shan; Yanan Yao; Feifei Peng; Shanshan Jiang; Dandan Yang; Guixia Ling; Peng Zhang (Drug Delivery and Translational Research, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Balanced stochastic versus deterministic assembly processes benefit diverse yet uneven ecosystem functions in representative agroecosystems - Wenjing Liu; Emily B. Graham; Yang Dong; Linghao Zhong; Jianwei Zhang; Chongwen Qiu; Ruirui Chen; Xiangui Lin; Youzhi Feng (Environmental Microbiology, 2021)
Summary Ecological assembly processes, by influencing community composition, determine ecosystem functions of microbiomes. However, debate remains on how stochastic versus deterministic assembly processes influence ecosystem functions such as carbon and nutrient cycling. Towards a better understanding, we investigated three types of agroecosystems (the upland, paddy, and flooded) that represent a gradient of stochastic versus deterministic assembly processes. Carbon and nutrient cycling multifunctionality, characterized by nine enzymes associated with soil carbon, nitrogen, phosphorous and sulfur cycling, was evaluated and then associated with microbial assembly processes and co‐occurrence patterns of vital ecological groups. Our results suggest that strong deterministic processes favour microorganisms with convergent functions (as in the upland agroecosystem), while stochasticity‐dominated processes lead to divergent functions (as in the flooded agroecosystem). To benefit agroecosystems services, we speculate that it is critical for a system to maintain balance between its stochastic and deterministic assembly processes (as in the paddy agroecosystem). By doing so, the system can preserve a diverse array of functional traits and also allow for particular traits to flourish. To further confirm this speculation, it is necessary to develop a systematic knowledge beyond merely characterizing general patterns towards the associations among community assembly, composition, and ecosystem functions.

Factors controlling organic carbon distributions in a riverine wetland - Junyu Dong; Di Zhao; Chao Zhang; Qingqing Cao; Jiaohui Fang; Ruirui Yang; Shuping Ji; Changchao Li; Ruiqi Zhao; Jian Liu (Environmental Science and Pollution Research, 2020)

Differences of the microbial community structures and predicted metabolic potentials in the lake, river, and wetland sediments in Dongping Lake Basin - Jiaohui Fang; Ruirui Yang; Qingqing Cao; Junyu Dong; Changchao Li; Quan Quan; Miansong Huang; Jian Liu (Environmental Science and Pollution Research, 2020)

A simple and low-energy method to prepare loratadine nanosuspensions for oral bioavailability improvement: preparation, characterization, and in vivo evaluation - Dandan Yang; Ruirui Li; Fang Zhang; Li Qin; Feifei Peng; Shanshan Jiang; Huiyang He; Xiumei Lu; Peng Zhang (Drug Delivery and Translational Research, 2020)

Cost-combined life cycle assessment of ferronickel production - Xiaotian Ma; Donglu Yang; Yijie Zhai; Xiaoxu Shen; Ruirui Zhang; Jinglan Hong (The International Journal of Life Cycle Assessment, 2019)

Environmental improvement of lead refining: a case study of water footprint assessment in Jiangxi Province, China - Donglu Yang; Yongquan Yin; Xiaotian Ma; Ruirui Zhang; Yijie Zhai; Xiaoxu Shen; Jinglan Hong (The International Journal of Life Cycle Assessment, 2019)

Effects of Urban–rural Atmospheric Environment on Heavy Metal Accumulation and Resistance Characteristics of Pinus tabulaeformis in Northern China - Ruirui Zhao; Tong Yang; Cong Shi; Meili Zhou; Guoping Chen; Fuchen Shi (Bulletin of Environmental Contamination and Toxicology, 2019)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Enhanced drought tolerance in tomato plants by overexpression of SlMAPK1 - Liu Wang; Ruirui Zhao; Rui Li; Wenqing Yu; Meijing Yang; Jiping Sheng; Lin Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Facilitation or Competition? The Effects of the Shrub Species Tamarix chinensis on Herbaceous Communities are Dependent on the Successional Stage in an Impacted Coastal Wetland of North China - Ning Du; Pan Wu; Franziska Eller; Dayou Zhou; Jian Liu; Wenhao Gan; Ruirui Yang; Min Dai; Yandong Chen; Renqing Wang; Weihua Guo (Wetlands, 2017)

The relationship between microvasculature in white matter hyperintensities and cognitive function - Jianzhong Sun; Xinfeng Yu; Yerfan Jiaerken; Ruirui Song; Peiyu Huang; Chao Wang; Lixia Yuan; Yingying Mao; Yang Guo; Hualiang Yu; Minming Zhang (Brain Imaging and Behavior, 2017)

Toxicity bioassays for water from black-odor rivers in Wenzhou, China - He DeFu; Chen RuiRui; Zhu EnHui; Chen Na; Yang Bo; Shi HuaHong; Huang MinSheng (Environmental Science and Pollution Research, 2015)

Quantitative effects of wind erosion on the soil texture and soil nutrients under different vegetation coverage in a semiarid steppe of northern China - Yuchun Yan; Xiaoping Xin; Xingliang Xu; Xu Wang; Guixia Yang; Ruirui Yan; Baorui Chen (Plant and Soil, 2013)